High-serum carotenoids associated with lower risk for developing type 2 diabetes among Japanese subjects: Mikkabi cohort study. Issue 1 (1st December 2015) - Sugiura, Minoru; Nakamura, Mieko; Ogawa, Kazunori; Ikoma, Yoshinori; Yano, Masamichi
Abstract : Objective: Recent epidemiological studies show the association of antioxidant carotenoids with type 2 diabetes, but thorough longitudinal cohort studies regarding this association have not been well conducted. The objective of this study was to investigate longitudinally whether serum carotenoids are associated with the risk for developing type 2 diabetes among Japanese subjects. Research design and methods: We conducted a follow-up study on 1073 males and females aged 30–79 years at the baseline from the Mikkabi prospective cohort study. Those who participated in the baseline and completed follow-up surveys were examined longitudinally. Over the 10-year period, 910 subjects (295 males and 615 females) took part in the follow-up survey at least one time. A cohort of 264 males and 600 females free of diabetes at baseline was studied. Results: Over a mean follow-up period of 7.8 years (SD=2.9), 22 males and 33 females developed new type 2 diabetes. After adjustments for confounders, the HRs for type 2 diabetes in the highest tertiles of serum α-carotene, β-cryptoxanthin, and total provitamin A carotenoids against the lowest tertiles were 0.35 (95% CI 0.15 to 0.82), 0.43 (CI 0.20 to 0.92) and 0.41 (CI 0.19 to 0.90), respectively. For β-carotene and zeaxanthin, borderline reduced risks were also observed, but these were not significant. Conclusions: Our results further support the hypothesis that eating a diet rich in carotenoids, especially provitamin A carotenoids, might help prevent the development of type 2 diabetes in Japanese patients. Trial registration number: NIFT-2013001.